Who is Vasily Travnikov? Between Literary Hoax and Literary History - Akifumi Takeda (Studia Litterarum)
The Life of Vasily Travnikov (1936) by V. Khodasevich is a literary hoax that introduces a fictional poet, the predecessor of Pushkin, and plausibly tells about his life and work. This character is Khodasevich’s twin of a kind who criticizes literature of the pre-Pushkin era and the initial period of Pushkin’s literary career and claims to create a “Travnikov tradition” comparable to the “Pushkin tradition.” Thus, The Life of Vasily Travnikov is an attempt at “myth creation” typical for the modernist literature. Though the image of Travnikov is not purely autobiographical, it gives an idea about Khodasevich, his poetic work and worldview better than, for example, his famous memoirs Necropolis.